Effects of temperature and light on methane production of widespread marine phytoplankton - Klintzsch, Thomas; Langer, Gerald; Wieland, Anna; Geisinger, Hannah Katharina; Lenhart, Katharina; Nehrke, Gernot; Keppler, Frank (Journal of geophysical research. Biogeosciences, 2020)
Methane (CH4) production in the ocean surface mixed layer is a widespread but still largely unexplained phenomenon. In this context marine algae have recently been described as a possible source of CH(4)in surface waters. In the present study we investigated the effects of temperature and light intensity (including daylength) on CH(4)formation from three widespread marine algal speciesEmiliania huxleyi,Phaeocystis globosa,andChrysochromulinasp. Rates ofE. huxleyiincreased by 210% when temperature increased in a range from 10 degrees C to 21.5 degrees C, while a further increase in temperature (up to 23.8 degrees C) showed reduction of CH(4)production rates. Our results clearly showed that CH(4)formation ofE. huxleyiis controlled by light: When light intensity increased from 30 to 2,670 mu mol m(-2) s(-1), CH(4)emission rates increased continuously by almost 1 order of magnitude and was more than 1 order of magnitude higher when the daylength (light period) was extended from 6/18 hr light-dark cycle to continuous light. Furthermore, light intensity is also an important factor controlling CH(4)emissions ofChrysochromulinasp. andP. globosaand could therefore be a species-independent regulator of phytoplankton CH(4)production. Based on our results, we might conclude that extensive blooms ofE. huxleyicould act as a main regional source of CH(4)in surface water, since blooming ofE. huxleyiis related to the seasonal increase in both light and temperature, which also stimulate CH(4)production. Under typical global change scenarios,E. huxleyiwill increase its CH(4)production in the future. Plain Language Summary Methane is a gas that affects the Earth's climate and is typically produced by microbes in the absence of oxygen or through geological processes. Surprisingly, methane is also produced in oceanic surface waters that are well oxygenated, known as the ocean-methane paradox. Marine phytoplankton has recently been discovered as a methane source, which might help to explain the paradox. Environmental factors such as light and temperature might be important for controlling methane production from marine algae. In order to understand how environmental factors affect methane formation from phytoplankton, we performed several experiments under laboratory conditions. We find that temperature, light intensity, and day length strongly control methane production of phytoplankton. The field blooms of marine algae, which are often strongly related to the seasonal increase of light and temperature, could act as an important regional source of methane in oceanic surface waters. Under typical global change scenarios, marine algae might increase their methane production in the 21th century.
Gesehen am 27.11.2020